Examining the behaviour of inflation to supply and demand shocks using an MS-VAR model - Koursaros, Demetris; Michail, Nektarios A.; Savva, Christos S. (My University, 2024)
This paper examines how inflation reacts depending on whether a supply (cost) or demand (markup) shock occurs. Despite their importance, the behaviour of markups remains an open empirical question in the literature. We use data for the US over the 1948q1-2019q3 period, decompose the price index to markups and costs, and employ a small-scale DSGE model to extract identifying size conditions for the coefficient estimates. These are then used in a Markov-switching VAR (MS-VAR) with fixed transition probabilities using an updating step. The empirical exercise shows that three different regimes exist (expansionary, contractionary, supply shock), while the Generalized Impulse Response Functions document that markups appear to be countercyclical and marginal costs are procyclical across all regimes. As such, inflation's reaction to a shock can be less volatile than expected depending on the regime. In addition, larger shocks have a lower and less persistent effect on inflation, because they are more easily identifiable, allowing corrective action to be taken.
Keywords: Markov-switching; Inflation; Markup; Marginal cost; Asymmetry; GIRF